Specific Aspects Of Concepts That Represent Human Mental Activity - Eshtuhtarova Bibigul Bektashevna (Zien Journals, 2022)
This article analyses the concept of "mind", "mentality", "consciousness", "knowledge", "thought", "memory", "intellect" in English, and the opinions about them. In addition, definitions are compared with the Uzbek language.
Keywords: Concept; Mind; Mentality; Consciousness